Action Potential Prolongation, β-Adrenergic Stimulation, and Angiotensin II as Co-factors in Sarcoplasmic Reticulum Instability - Ronchi, Carlotta; Badone, Beatrice; Bernardi, Joyce; Zaza, Antonio (Frontiers in Physiology, 2019)
Increases in action potential duration (APD), genetic or acquired, and arrhythmias are often associated; nonetheless, the relationship between the two phenomena is inconstant, suggesting coexisting factors. -adrenergic activation increases sarcoplasmic reticulum (SR) Ca2+-content; angiotensin II (ATII) may increase cytosolic Ca2+ and ROS production, all actions stimulating RyRs opening. Here we test how APD interacts with β-adrenergic and AT-receptor stimulation in facilitating spontaneous Ca2+ release events (SCR). Methods: under “action potential (AP) clamp”, guinea-pig cardiomyocytes (CMs) were driven with long (200 ms), normal (150 ms), and short (100 ms) AP waveforms at a CL of 500 ms; in a subset of CMs, all the 3 waveforms could be tested within the same cell. SCR were detected as inward current transients (ITI) following repolarization; ITI incidence and repetition within the same cycle were measured under increasing isoprenaline concentration ([ISO]) alone, or plus 100 nM ATII (30 min incubation+superfusion). Results: ITI incidence and repetition increased with [ISO]; at longer APs the [ISO]-response curve was shifted upward and ITI coupling interval was reduced. ATII increased ITI incidence more at low [ISO] and under normal (as compared to long) APs. Efficacy of AP shortening in suppressing ITI decreased in ATII-treated myocytes and at higher [ISO]. Conclusions: AP prolongation sensitized the SR to the destabilizing actions of ISO and ATII. Summation of ISO, ATII and AP duration effects had a “saturating” effect on SCR incidence, thus suggesting convergence on a common factor (RyRs stability) “reset” by the occurrence of spontaneous Ca2+ release events.